Antioxidant enzyme profile in chronic pelvic pain syndrome patients - Arısan, Serdar; Kiremit, Murat Can; Palavan-Ünsal, Narçin; Ergenekon, Erbil; ARISAN, ELİF DAMLA (İstanbul Kültür Üniversitesi Yayınları, 2007)
Chronic pelvic pain syndrome (CPPS) is a common and serious health problem affecting the quality of life in men. According to National Institute of Health classification system abacterial chronic pelvic pain has two sub category which are defined as 3a and 3b. The major difference between these two groups inflammation status. In this study we aim to investigate the antioxidant enzyme levels such as Glutathion peroxidase (Gsh-Px), superoxide dismutase (SOD), catalase (CAT) and lipid peroxidation products in CPPS patients. All enzyme levels were determined in patients and disease free control group blood samples by spectrophotometrically. In our study, the enzyme levels were not a good indicator for comparison of 3a or 3b type CPPS patients. However, Gsh-Px, SOD and lipid peroxidation products were significantly different from disease free control samples. Although high generation of H202 due to SOD activity, we did not detect any change in CAT activity in patients blood samples compare to control group.
Keywords: Prostatitis; superoxide dismutase; catalase; glutathion peroxidase; lipid peroxidase; prostatit; süperoksit dismutaz; katalaz; lipid peroksidaz; glütation peroksidaz